Bioma (Basic Information of Mangrove) sebagai Media Edukasi Pentingnya Tanggap Bencana dengan Vegetasi sebagai Pembatas Alami di Pekon Biha Pesisir Barat Lampung - Rizka Nabilah; Rian Adetiya Pratwi; Septi Maulidyah; Martin Muljana (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
Background: Pekon Biha Pesisir Barat is one of the villages directly adjacent to a body of sea water. This is a concern if it is not balanced with supporting information about the importance of mangrove habitat for rehabilitation. There is very little understanding of mangroves in this area. It can be seen from the people who carry out large-scale land conversion. This PKM aims to introduce the benefits of mangroves in a module with the BIOMA (Basic Information of Mangrove) concept as an effort to prevent disaster risk at SDN 1 Biha, Pekon Biha, Pesisir Barat Lampung. Methods: BIOMA is arranged based on tiered material that stimulates the sense of sight. The Village Partner is Pekon Biha, West Coast of Lampung. The method is carried out by teaching mangrove modules and interactive videos and evaluation through pre and post-test. Result: BIOMA mangrove education media received very high attention from elementary students, there was an increase in knowledge of 36% (very good). The pre-test showed that knowledge about mangroves in the good category was only 13%, after the provision of educational media, there were 76% of students who had very good knowledge about mangroves. The novelty of this PKM is creating interactive modules with live demonstrations with storylines that are close to the community. Conclusion: This media is effective in providing information related to mangroves.